STUDI EMPIRIS PERSEPSI PEMIMPIN PERUSAHAAN TENTANG GREEN BUSINESS PADA INDUSTRI GARMEN DI BOYOLALI, KLATEN, DAN YOGYAKARTA: ANALISIS FENOMENOLOGI INTERPRETIF - Palgunadi, Petrus; Sanjaya, Ridwan; Murniati, Cecilia Titiek (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2023)
Indonesia's ambition to realize a green economy, must be supported by the green business. However, from a study by the Ministry of Industry in 2012, there were still various definitions of the green industry. This study aims to explore the perceptions of garment company leaders towards green business, identify and analyze the impact of green business on company operations, and identify and analyze green industries practices in garment companies.This study uses a qualitative approach using Interpretive Phenomenological Analysis (IPA). The participants of this research are the top six leaders of the largest garment companies in Central Java and DIY that export their products to the global market. Data was collected through in-depth interviews, observations, and company documents. This research found that leaders who perceive green business for company efficiency have more green initiatives than leaders who perceive green business as a government program